The Effect of the Inlet Boundary Layer on the Secondary Flow in an Annular Cascade - Shammaa, El S.A. (My University, 1978)
The development of small gas turbine units with high specific output calls for the design and testing of rotor cascades with high turning blades. A major portion of the losses that occur in such cascades are associated with the secondary flow. The need for experimental data of highly loaded annular cascades can be readily seen from a review of the available literature.
The objective of this study was to construct and test an annular test rig of special configuration particularly suited for high turning blades. The rig was an open circuit wind tunnel with inlet and exit ducts of hyperboloidal shape. The test facility provided a means for adjusting the inlet flow in the circumferential direction (to ensure periodicity) as well as controlling the inlet endwall boundary layers. The cascade tests were conducted at a Reynolds number of 4.73x10⁵ based on the blade chord. Extensive flow measurements were taken at the inlet and the exit from the cascade both in the main stream and the endwall boundary layers. The passage walls static pressure distribution was also measured. Maps of the exit flow parameters were presented for the total pressure loss coefficient, static pressure coefficient and the secondary flow velocity vectors. The averaged flow parameters were analysed and the losses were compared with several predictive correlations. The measured losses were found comparatively lower than the predicted.
A flow visualization study was carried out using smoke in the air stream and oil film (lamp-black and kerosene) on the passage walls. The results thus obtained were consistent with the general flow picture depicted from the analysis of the measured data.
Keywords: Mechanical Engineering; Mechanical Engineering